A new species of Pseudococcus (Hemiptera: Pseudococcidae) belonging to the “Pseudococcus maritimus” complex from Chile: molecular and morphological description - Correa, Margarita; Aguirre, Carlos; Germain, Jean-François; Hinrichsen, Patricio; Zaviezo, Tania; Malausa, Thibaut; Prado, Ernesto (Zootaxa, 2011)
A new species of mealybug from Chile, Pseudococcus meridionalis Prado sp. n., is described and illustrated based on the morphological and molecular characterization of adult females. This species belongs to the “Pseudococcus maritimus” complex and displays a wide host plant range, including Japanese pear, persimmon, pomegranate, pear and grape.